Evaluasi Kelengkapan Resep Rawat Jalan terhadap Kepatuhan SOP Peresepan di Poli dalam Rumah Sakit MM Indramayu Tahun 2020 - Dinda Ayu Hardian Hartati; Rida Emelia (Syntax Corporation Indonesia, 2021)
in its writing, inclusion of information, improper prescription, and even incorrect prescription. The impact of these errors can lead to several factors that can be detrimental, ranging from the inaccuracy of drugs given to certain individuals, errors in measuring the dose given, or incompatibility of drugs with certain patients so that it can result in disability or death. This study aims to determine the completeness of outpatient prescriptions according to prescribing SOP compliance served in the internal disease polyclinic of MM Indramayu Hospital. This study used a descriptive method which was carried out retrospectively using activity data for the period January - December 2020. Sampling was carried out using the Slovin formula and obtained 380 recipes. Based on the data collection and analysis carried out in this evaluation, it can be seen that the administrative completeness of prescriptions that meet the requirements are (74.73%), while the administrative completeness of prescriptions that do not meet the requirements are (25.26%). Administrative documents that meet the criteria are Signature, Incryptio, Invocation, Patient Name and Age (100%), while other administrations are Praescriptio/Ordonatio (28.68%), Subscriptio (45.26%), and Address (75.78%). From this evaluation, it can be concluded that many outpatient prescriptions meet the completeness aspect of the prescription SOP at MM Indramayu Hospital. However, improvements in prescribing need to be done so that there are no prescriptions that do not meet the requirements. This can be done by reviewing doctors to be more thorough and clear in prescription writing, communication between pharmacists and doctors or medical audits of prescription writing